Prognostic Value of Programmed Cell Death 1 Ligand-1 in Patients With Bone and Soft Tissue Sarcomas: A Systemic and Comprehensive Meta-Analysis Based on 3,680 Patients - Wang, Feng; Yu, Tao; Ma, Chengbin; Yuan, Hongmou; Zhang, Haifei; Zhang, Zhiyu (Frontiers in Oncology, 2020)
Background: Programmed cell death 1 ligand-1 (PD-L1) is an immune checkpoint molecule that acts to protect cancer cells from immune surveillance and is considered a prognostic biomarker in several cancers, but the prognostic value of PD-L1 remains inconclusive in bone and soft tissue sarcomas. In the present meta-analysis, the clinicopathological and prognostic value of PD-L1 in sarcomas was evaluated. Method: We performed a systemic and comprehensive meta-analysis by searching the PubMed, Medline, Cochrane Library, EMBASE and Web of Science databases up to October 31, 2019. Eligible articles were incorporated, and pooled hazard ratios (HRs) and odds ratios (ORs) with their 95% confidence intervals (CIs) were used to estimate the outcomes. Results: Thirty-six articles containing 39 independent studies with 3,680 bone and soft tissue sarcoma patients were included in our meta-analysis. The pooled results showed that PD-L1 overexpression could predict poor OS (HR 1.45, 95% CI 1.11-1.90, P < 0.01), MFS (HR 1.58, 95% CI 1.14-2.19, P < 0.01) and EFS (HR 2.82, 95% CI 1.69-4.71, P < 0.01) in sarcomas. Furthermore, PD-L1 overexpression was correlated with a higher rate of tumour metastasis (OR 2.95, 95% CI 1.32- 6.60, P < 0.01), a more advanced tumour grade (OR 3.63, 95% CI 2.55-5.16, P < 0.01) and more T lymphocyte infiltration (OR 5.55, 95% CI 2.86-10.76, P < 0.01). No obvious publication bias was observed, and the sensitivity analysis showed that our results were robust. Conclusion: The results of our meta-analysis indicate that high PD-L1 expression might serve as a valuable and predictive biomarker for adverse clinicopathological features and poor prognosis in patients with sarcoma.